ANALYSIS OF DIABETES MELITES DISEASE USING BINARY LOGISTIC REGRESSION - Anistya, Mery; Putroue Keumala Intan; Ahmad Hanif Asyhar; Wika Dianita Utami (Jurnal Statistika dan Aplikasinya, 2025)
This study aims to identify risk factors that affect the incidence of diabetes mellitus and evaluate the accuracy of the prediction model using binary logistic regression. The research method used secondary data from 140 patients at UPT Puskesmas Teja, Pamekasan, consisting of 60 diabetes negative patients and 80 diabetes positive patients. The variables analyzed included age, gender, heredity, smoking habit, body mass index (BMI), blood glucose level, cholesterol, and blood pressure. The results showed that the variables of gender and glucose levels had a significant influence on the incidence of diabetes, with significance values of 0.022 and 0.001, respectively. The gender variable has an Odds Ratio (OR) value of 0.135, indicating that female patients tend to have a lower risk of developing diabetes than men. Meanwhile, glucose levels showed a positive association with the incidence of diabetes, with each unit increase in glucose levels increasing the risk of diabetes by 1.016 times. The binary logistic regression model developed has an accuracy of 87.1% based on the Area Under Curve (AUC) value, which falls into the category of strong classification ability. This study provides important implications in supporting the development of more effective diabetes prevention and management strategies through an in-depth understanding of risk factors, so that it can be used as a basis for decision-making in public health services.